Arts management : uniting arts and audiences in the 21st century - Rosewall, Ellen (2014)
"Designed for students and practitioners with little experience in not-for-profit management, Arts Management provides an indispensable guide to the theory and practice of managing arts and cultural organizations. This concise text engages readers with case studies and critical-thinking exercises that will develop their ability to adapt to a changing industry. From governance and human resources to program development, financial management, and marketing, Arts Management addresses the unique atmosphere of managing the arts today. It meets the standards of the AAAE (Association of Arts Administration Educators) guaranteeing that both current and future practitioners will be prepared to meet the challenges of managing today's arts organizations"--
"Arts Management is a text designed for undergraduate or graduate arts management students. It provides an overview of topics that are standard in arts management study, including organizational structure, governance, management, human resources, fundraising, marketing, and advocacy"--
Machine generated contents note: -- Introduction -- Acknowledgements -- 1. What is Arts Management? -- Defining the arts -- Defining culture -- Defining arts management -- Organizing the arts through history -- The arts in America -- The arts in contemporary society -- 2. Management and Leadership -- Management today -- The four functions of management -- Historical development of management: 1776-1920 -- Historical development of management: 1920-2000 -- Management and the arts organization -- Leadership vs. management -- 3. Organizational Structure -- Philosophy of organizational structure -- For-profit business (aka the "private sector") -- Government (aka the "public sector") -- Not-for-profit (aka the "social sector") -- Not-for-profit regulations and benefits -- Alternative structures -- Choosing a structure -- Forming an arts not-for-profit -- 4. Planning -- Why plan? -- Why not plan? -- Types of plans -- Mission, vision and values -- Assessing the organization: situational analysis -- Creating the plan: goals, objectives and strategies -- Managing the planning process -- 5. Governance and the Board of Directors -- Governance vs. management -- The not-for-profit board of directors -- Types of boards -- Fiduciary duty -- Governing responsibilities of the board of directors -- Responsibilities of the individual board member -- The role of the board in fund-raising -- Committees of the board -- Relationship of board and staff -- Recruiting board members -- 6. Personnel and Volunteer Management -- The not-for-profit workforce -- Which types of staff should be hired? -- The Organizational Chart -- Personnel management -- Volunteers in the arts organization -- 7. Program Planning and Evaluation -- Mission-based program planning -- Functions of arts organizations -- Artistic considerations in planning -- Audience and community considerations -- Defining success -- Determining feasibility -- Evaluating programs -- 8. Financial Management, Part 1 -- Financial distinctions of not-for-profit businesses -- Financial management terms and concepts -- Financial management systems -- Chart of accounts -- Types of financial statements -- 9. Financial Management, Part 2 -- Indicators of financial health -- Internal controls -- The financial management cycle -- Budgeting -- Planning and accounting for contributed income -- Fund accounting -- Planning and accounting for earned income -- Auxiliary business ventures -- Asset management -- 10. Fundraising, Part 1: The Basics -- What is fundraising? -- The fundraising mentality -- Preparation for successful fundraising -- Who gives to the arts? -- Government's role in arts support -- 11. Fundraising, Part 2: From Theory to Practice -- Donor relations and fundraising ethics -- Prospect research -- The annual campaign -- Writing a successful fundraising letter -- Successful grant writing -- Soliciting corporate sponsorship -- 12. Education and the arts -- Defining basic terms -- The arts and human development -- Arts education in the school setting -- Education in the arts organization -- 13. Marketing and Audience Development -- Challenges of marketing the arts -- The marketing mindset -- Understanding arts audiences -- Has technology hurt arts attendance? -- How consumer behavior affects marketing -- Marketing trends and practices -- The impact of social media -- Audience development -- Marketing planning -- Marketing research -- 14. Marketing Techniques -- Target marketing -- Positioning -- Communicating the message -- The Marketing Mix -- Product -- Place -- Price -- Promotion -- Public Relations -- Advertising -- Sales Promotion -- 15. Community Engagement -- What is community engagement? -- Challenges of community engagement -- Community arts development -- Social and civic benefits of arts and culture -- Arts in the economy -- Public art -- 16. Arts Advocacy -- Government and the arts -- The arts in the United States -- Advocacy -- Making the case for the arts -- Getting started in legislative advocacy -- Developing effective messages -- Appendices -- Appendix I: Sample template for an arts business plan -- Appendix II: Strategic plan template -- Appendix III: Commitment to serve -- Appendix IV: Volunteer job description -- Appendix V: Sample chart of accounts -- Appendix VI: Child's Play Statement of Activities -- Appendix VII: Child's Play Financial position -- Appendix VIII: Child's Play budget -- Appendix IX: Child's play program report -- Appendix X: Dairyland Arts Council grant application -- Appendix XI: Sample appeal letter -- Appendix XII: Sample media release -- Appendix XIII: Sample advocacy letter -- Appendix XIV: Arts service organizations -- Glossary -- Index.
Includes bibliographical references and index.
Keywords: Arts -- Management -- Textbooks; ART / General; ART / Business Aspects